The stickiness of national competitiveness: Implications for Switzerland and beyond - Stephan Mumenthaler; Barbara von Schnurbein (Aussenwirtschaft, 2016)
This paper postulates that a country's competitiveness is sticky, i.e. it does not react immediately to changes in underlying framework conditions. The causes of this stickiness can be categorized along three dimensions. First, there is a delay between policy actions and their impact on competitiveness ("pipeline effect"). Second, visible reactions of firms to changes in framework conditions lag behind insofar as firms react relatively quickly on the margin, i.e. with new projects, but react only slowly with existing activities due to sunk-cost effects ("overflow effect"). Third, as politics reacts only to visible changes in competitiveness, and given that these actions again need time to take effect, reactions are systematically delayed. Policymaking should take into account all three of these dimensions of stickiness to prevent major damage to a country's competitiveness. This is especially relevant in a small open economy like Switzerland, as the relatively small size of the home market compared to exports amplifies the effect of changes in framework conditions on competitiveness. We therefore conclude by presenting policy measures to help anticipate and dissipate the negative effects of stickiness.
Keywords: R11; R38; R58; 330; Policy making; Competitiveness; Region